Dental lessons from past to present: ultrastructure and composition of teeth from plesiosaurs, dinosaurs, extinct and recent sharks1. Issue 76 (19th August 2015) - Lübke, A.; Enax, J.; Loza, K.; Prymak, O.; Gaengler, P.; Fabritius, H.-O.; Raabe, D.; Epple, M.
<x xml:space="preserve">Abstract</x> Sharks and dinosaurs used fluoroapatite in their teeth, unlike their contemporary relatives, as shown by a comprehensive analysis of the composition and structure of their fossilized teeth.